Stasis in the Medieval West?
XI, 283 p. 8 illus., 5 illus. in color.
Keywords: This volume questions the extent to which Medieval studies has emphasized the period as one of change and development through reexamining aspects of the medieval world that remained static. The Medieval period is popularly thought of as a dark age, before the flowerings of the Renaissance ushered a return to the wisdom of the Classical era. However, the reality familiar to scholars and students of the Middle Ages – that this was a time of immense transition and transformation – is well known. This book approaches the theme of ‘stasis’ in broad terms, with chapters covering the full temporal range from Late Antiquity to the later Middle Ages. Contributors to this collection seek to establish what remained static, continuous or ongoing in the Medieval era, and how the period’s political and cultural upheavals generated stasis in the form of deadlock, nostalgia, and the preservation of ancient traditions.